2017
DOI: 10.1177/0886260517741210
|View full text |Cite
|
Sign up to set email alerts
|

The Complexities of Intimate Partner Violence: Mental Health, Disabilities, and Child Abuse History for White, Indigenous, and Other Visible Minority Canadian Women

Abstract: This research examines how mental health issues associated with intimate partner violence (IPV) relate to women's intersecting identities of race/ethnicity, disability status, and child abuse history. Data ( N = 595) from a Canadian triprovincial study included women who were White ( n = 263, 44.8%), Indigenous ( n = 292, 49.7%), or visible minority ( n = 32, 5.5%). Few demographic differences were found. None of the mental health measures (Symptom Checklist-Short Form [SCL-10], Centre for Epidemiological Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
0
8
1
Order By: Relevance
“…Women with both IPSA and child sexual abuse histories had significantly higher mental distress on the SCL-10 (in the clinical range; congruent with Cole et al, 2005) than women with no CSA or IPSA history or than women with IPSA-only but the effect size was negligible. This contrasts with an analysis of the data for the original study (Tutty et al, 2021) in which mental distress was not in the clinical range when considering intimate partner violence, suggesting the impact of sexual assaults from partners on this more global measure of mental health functioning and psychological distress in the previous week.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…Women with both IPSA and child sexual abuse histories had significantly higher mental distress on the SCL-10 (in the clinical range; congruent with Cole et al, 2005) than women with no CSA or IPSA history or than women with IPSA-only but the effect size was negligible. This contrasts with an analysis of the data for the original study (Tutty et al, 2021) in which mental distress was not in the clinical range when considering intimate partner violence, suggesting the impact of sexual assaults from partners on this more global measure of mental health functioning and psychological distress in the previous week.…”
Section: Discussioncontrasting
confidence: 69%
“…Aside from studies that identify women with mental health difficulties as more vulnerable to IPSA, none of the reviewed studies examined disability and intimate partner sexual assaults. The original studies with this data set also identified the importance of disability as linked to difficult mental health symptomology both at baseline (Tutty et al, 2021) and longitudinally (Tutty et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Healing Journey commenced in 2005, with data collected every 6 months over 3.5 years. To provide a baseline for the subsequent longitudinal data analysis (Tutty et al, 2017), the current descriptive data were from the first two waves (constituting the complete study protocol, broken into two waves because of length). The questionnaires were administered face-to-face, with female interviewers reading the questions and recording answers to ameliorate any problems with literacy.…”
Section: Research Proceduresmentioning
confidence: 99%